The Influence of Procedural Justice on Work Engagement And Turnover Intention - Atmaja, Dodi Ria; Marika, Lidya (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
To attain long-term growth and maintain a competitive edge in light of swift technological and environmental transformations, the organization is presently concentrating on generating novel values through the implementation of diverse personnel management systems and an innovative organizational structure. The principal objective of this research is to ascertain whether organizational commitment has a substantial influence on the operation of a company's system and to investigate the consequences of interrelationships among pre-existing variables. Purposive sampling is a non-probability sampling technique that is employed in this investigation. The cumulative number of participants (120) was determined by employing the methodology suggested by Hair et al. (2019), which required the multiplication of n by 5. The study's eligible participants are personnel from the marketing department who fall within the age range of 18 to 45 years. The analytics method utilized is Partial Least Square Structural Equation Modeling (PLS-SEM). It is possible to conclude, on the basis of the research findings, that procedural justice increases organizational trust. Work engagement is positively influenced by procedural justice, which subsequently has a positive impact on organizational commitment. An organization's level of trust has a positive effect on employee engagement. Labor engagement and organizational commitment are correlated in a positive way. Trust within an organization has a constructive influence on members' level of commitment. Work engagement is not influenced by organizational trust in the context of the organization's procedural justice. A negative correlation has been observed between attrition intention and procedural justice. Organizational commitment mediates the relationship between procedural justice and attrition intention. Organizational commitment has a statistically significant and negative effect on attrition intention. Procedural justice significantly and positively mediates the relationship between organizational trust and organizational commitment; however, organizational commitment does not mediate the relationship between procedural justice and work engagement.